ANALISIS MATA PELAJARAN FIKIH KELAS X MATERI ZAKAT DAN HIKMAHNYA DI MADRASAH ALIYAH - Zubaidillah, Muh Haris (Al-Falah: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2018)
National education functions to develop the ability and shape of dignified national character and civilization in order to educate the life of the nation, aims to develop the potential of students to become faithful and fearful people of God Almighty, noble, healthy, knowledgeable, capable, creative, independent and become a democratic and responsible citizen. To achieve this goal, one of the fields of study that must be learned by students in madrasas is Islamic Religious Education (PAI). Jurisprudence education is one of the Islamic religious education that is applied in educational institutions, ranging from basic education to Islamic higher education as a means of realizing educational goals, forming people who understand the Islamic shari'ah. This article tries to analyze the subject matter of X-class fiqh material and its wisdom in Madrasah Aliyah from the aspect of conformity between material content and core competencies and basic competencies, between material and social development and children's intelligence, between learning materials and methods and also between material and evaluation. Keywords: Analysis, Zakat, Fiqh, Madrasa Aliyah